Relationship between fibroblast growth factor in plasma and carotid plaque neovascularization: a pilot study - Zamani, Mahtab; Skagen, Karolina; Lindberg, Beate; Bjerkeli, Vigdis; Aukrust, Pål; Halvorsen, Bente; Skjelland, Mona (Frontiers in Immunology, 2024)
Background: Unstable atherosclerotic carotid plaques with intraplaque neovascularization (IPN) carry a substantial risk for ischemic stroke. Conventional ultrasound methods fall short in detecting IPN, where superb microvascular imaging (SMI) has emerged as a promising tool for both visualizing and quantification. High levels of fibroblast growth factor 23 (FGF-23) have, in observational studies, been suggested as related to cardiovascular morbidity and mortality. The association of FGF-23 to atherosclerotic carotid plaque instability remains relatively unexplored. Methods: A cohort of twenty-nine patients with ≥50% atherosclerotic carotid stenosis underwent conventional carotid ultrasound, SMI, and blood tests, including measurement of FGF-23 in plasma. Nineteen patients were characterized as symptomatic and ten as asymptomatic. Results: Our major findings were: i) Higher FGF-23 levels were strongly correlated with increased SMI-assessed IPN. ii) Neo-vessel count recorded by quantitative SMI was positively correlated to increased FGF-23 levels, but not with basic FGF levels. (iii) In contrast, traditional risk factors for plaque instability exhibited no noteworthy associations with SMI-assessed IPN or with FGF-23 levels. Conclusions: This pilot study suggest the potential of FGF-23 as a valuable marker for neovascularization and atherosclerotic carotid plaque instability as a risk factor for ischemic stroke. Further research involving larger cohorts and prospective data is necessary to understand FGF-23's role in this context comprehensively.